Peran Guru dalam Penerapan Pembelajaran Berdiferensiasi untuk Menumbuhkan Minat Belajar Siswa pada Mata Pelajaran Sosiologi - Lisnawati, Lilis; Kuntari, Septi; Hardiansyah, Muhammad Agus (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Students' interest in the subject of sociology varies, and some of them may be less enthusiastic about the subject, so an approach that caters to individual students' needs is necessary. The aim of this research is to outline the crucial role of teachers in implementing differentiated learning strategies in sociology and its impact on enhancing students' interest in the subject. This study utilizes a qualitative approach using a descriptive methodology, and data is gathered through observations, interviews, and document analysis. The research is carried out at SMAN 2 Pandeglang, located in the Banten Province. The research findings reveal several key points: (1) Teachers apply various customized learning strategies, such as grouping students based on their abilities, providing diverse learning resources, and assigning projects that align with students' interests. (2) Teachers act as facilitators, assisting students in identifying their interests, providing guidance, and challenging students according to their individual abilities. (3) The outcome of implementing differentiated learning is that students become more engaged in the learning process because they perceive the subject matter as relevant to their interests and personal experiences. In conclusion, the role of teachers is pivotal in cultivating students' interest in sociology at SMAN 2 Pandeglang through the implementation of tailored learning strategies. Teachers need to function as facilitators who understand students' needs and interests to create an inclusive and engaging learning environment.